Long-term follow-up from a phase 1/2 study of single-agent bortezomib in relapsed systemic AL amyloidosis - Reece, Donna E.; Hegenbart, Ute; Sanchorawala, Vaishali; Merlini, Giampaolo; Palladini, Giovanni; Bladé, Joan; Fermand, Jean-Paul; Hassoun, Hani; Heffner, Leonard; Kukreti, Vishal; Vescio, Robert A.; Pei, Lixia; et al. (Blood, 2014)
Key Points. Single-agent bortezomib produces durable hematologic responses and promising long-term overall survival in relapsed AL patients.Once-weekly bortezo
Gesehen am 06.07.2020